2016
DOI: 10.4114/ia.v18i56.1159
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Defect Prediction Framework using Genetic Algorithms: A Validation of Empirical Studies

Abstract: Today, it is common for software projects to collect measurement data through development processes. With these data, defect prediction software can try to estimate the defect proneness of a software module, with the objective of assisting and guiding software practitioners. With timely and accurate defect predictions, practitioners can focus their limited testing resources on higher risk areas. This paper reports the results of three empirical studies that uses an automated genetic defect prediction framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This way, the performance of the application should be improved visibly, which would make real-time detection become more of a possibility than a probability. Furthermore, we would also like to explore various alternatives to the currently-implemented perceptron classifier, such as genetic algorithms [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This way, the performance of the application should be improved visibly, which would make real-time detection become more of a possibility than a probability. Furthermore, we would also like to explore various alternatives to the currently-implemented perceptron classifier, such as genetic algorithms [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Murillo-Morera J et al (2016) reported the results of empirical studies using an automated genetic defect prediction framework. The framework generates and compares different learning schemes using a genetic algorithm to estimate the defect proneness of software modules, demonstrating similar performance between frameworks and better runtime compared to an exhaustive framework [34]. Arora R et al (2022) introduced a framework for heterogeneous fault prediction (HFP) using feature selection and supervised learning algorithms.…”
Section: A Software Fault Predictionmentioning
confidence: 99%